Pediatric solid organ injury – frequency of abdominal imaging is determined by the treating department. Issue 45 (6th November 2020) - Zimmermann, Peter; Schmidt, Torben; Nelson, Jana; Gosemann, Jan-Hendrik; Bassler, Stefan; Stahmeyer, Jona T.; Hirsch, Franz Wolfgang; Lacher, Martin; Zeidler, Jan
Abstract : Abstract: To investigate the use of abdominal CT scanning in the management of pediatric blunt abdominal trauma in pediatric and non-pediatric departments. In this observational cohort study, anonymized data were extracted from 2 large German statutory health insurances (∼5.9 million clients) in a 7-year period (2010–2016). All patients with inpatient International Classification of Diseases (ICD) codes S36.- and S37.- (injury of intra-abdominal organs; injury of urinary and pelvic organs) aged ⩽18 years were included. Demographic and clinical data were analyzed by logistic regression analysis for associations with the use of abdominal CT. A total of 524 children with blunt abdominal trauma (mean age 11.0 ± 5.2 years; 62.6% males) were included; 164 patients (31.3%) received abdominal CT-imaging. There were no significant differences in traumatic non-intraabdominal comorbidity patterns (injuries of external causes; injuries to the head or thorax). There was substantial variability in the rate of abdominal CT imaging among different medical disciplines ranging from 11.6% to 44.5%. Patients admitted to pediatric departments (Pediatrics and Pediatric Surgery) underwent abdominal CT imaging significantly less frequently (19.7%; N = 55) compared to patients treated in non-pediatric departments (General/Trauma Surgery: 44.5%; N = 109) irrespective of concomitant injuries. The estimated OR for the use of abdominal CT by General/Trauma Surgery was 6.2-fold higher (OR: 6.15 [95-%-CI:3.07–13.21]; P  < .001) compared to Pediatric Surgery. Other risk factors associated with the use of abdominal CT were traumatic extra-abdominal comorbidities, increasing age, male gender, and admission to a university hospital. Abdominal CT imaging was significantly less frequently used in pediatric departments. The substantial variability of the abdominal CT rate among different medical disciplines and centers indicates a potential for reduction of CT imaging by implementation of evidence-based guidelines. Furthermore, our study underlines the need for centralization of pediatric trauma care in Germany not only to improve patient outcome but to avoid radiation-induced cancer mortality. Abstract : Supplemental Digital Content is available in the text